2018
DOI: 10.3233/ch-170361
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological and metabolic consequences of renal ischemia-reperfusion and their modulation by N,N-dimethyl-tryptamine on a rat model

Abstract: Metabolic and micro-rheological parameters impair during renal I/R. DMT could reduce but not completely prevent the changes in this rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…DMT can also induce neuronal plasticity, a longer duration brain recuperative and repair process (Tsai et al 2009;Ruscher et al 2011;Kourrich et al 2012;Ly et al 2018;Olson 2018Olson , 2021. DMT has been shown to reduce infarct size and improve functional recovery following transient focal brain ischemia in rats (Nardai et al 2020), suggesting possible efficacy in post-ischemia and in stroke treatment or prevention and to prevent renal ischemia-reperfusion injury in a rat model as well (Peto et al, 2018;Nemes et al 2019). Sigma-1 receptors can also regulate cell survival and proliferation (Collina et al 2013;Frecska et al 2013).…”
Section: The In Vivo and In Vitro Effects Of Exogenous Dmtmentioning
confidence: 99%
“…DMT can also induce neuronal plasticity, a longer duration brain recuperative and repair process (Tsai et al 2009;Ruscher et al 2011;Kourrich et al 2012;Ly et al 2018;Olson 2018Olson , 2021. DMT has been shown to reduce infarct size and improve functional recovery following transient focal brain ischemia in rats (Nardai et al 2020), suggesting possible efficacy in post-ischemia and in stroke treatment or prevention and to prevent renal ischemia-reperfusion injury in a rat model as well (Peto et al, 2018;Nemes et al 2019). Sigma-1 receptors can also regulate cell survival and proliferation (Collina et al 2013;Frecska et al 2013).…”
Section: The In Vivo and In Vitro Effects Of Exogenous Dmtmentioning
confidence: 99%
“…Hemorheological changes such as hypercoagulability, hyperviscosity and slow blood flow could accelerate renal impairment [21]. This study showed that hematocrit, erythrocyte aggregation index and erythrocyte count were significantly increased in DN rats.…”
Section: Discussionmentioning
confidence: 98%
“…The blood samples were obtained from heart and heparin anticoagulant tubes were used as the sampling tubes. The systematical changes of hemorheology of all rats were investigated by SA-5600 automatic hemorheology detector (Succeeder, China) [21].…”
Section: Methodsmentioning
confidence: 99%
“…DMT also contributes to increased expression of delta opioid receptors, which play a key role in providing tissue resistance to loss of blood flow and oxidative stress (Zhang et al, 2006). DMT has been found to alleviate the effects of ischaemia-reperfusion injury (IRI) caused by hypoxia, oxidative stress and inflammation in preclinical models of kidney transplantation (Peto et al, 2018). The anti-inflammatory protective effect of DMT may represent a new, more beneficial method of reducing IRI-induced damage during organ transplantation.…”
Section: { Dmt-induced Immunomodulationmentioning
confidence: 99%